Verification experiment of stocking and disposal tasks by automatic shelf and mobile single-arm manipulation robot. (17th September 2022) - Tanaka, Junya; Yamamoto, Daisuke; Nakashima, Ryo; Yamaji, Yuto; Ohtsu, Hiroshi; Kamata, Keisuke; Nara, Kohei; Asayama, Tetsuya
Abstract : This study proposes a stock handling system that combines an automatic shelf and a picking robot with the aim of reducing the labor required for stocking and disposing of items. The robot system was developed by referring to the rules of the robot competition WRS2020 F.C.S.C. The picking robot is a standard single-arm mobile manipulation robot and the automatic shelf is characterized by the fact that the shelves move up and down and back and forth automatically. Automatic movement of the shelves in the pull-out direction allows the end-effector of the manipulator to approach the item from above and select the grasping position from a number of candidates. This improves the stability of the grasping of the item and is expected to prevent the item from falling during transportation. When there are tall items at the front of the shelf, the end-effector can directly approach the items at the back of the shelf from above the shelf as the shelf plate automatically moves in the pull-out direction. We report the mechanical configuration of the automatic shelf and basic experimental results for stocking and disposal work by the proposed robot system. GRAPHICAL ABSTRACT: UF0001